When a Doctor Knows, It Shows: An Empirical Analysis of Doctors’ Responses in a Q&A Forum of an Online Healthcare Portal - Khurana, Sandeep; Qiu, Liangfei; Kumar, Subodha (Information Systems Research, 2019)
Healthcare portals are gaining in popularity, connecting doctors with potential consumers of healthcare services. As online search and transaction marketplaces, they bring both sides of the market onto the same platform. Managers or platform owners seek to create value by increasing the number of users on either side of demand and supply of services. User-generated activity on Q&A forums of such sites reduces information asymmetry and indicates an increased adoption by either side. In this study, we have provided insights into understanding drivers for increased recommendations for doctors in online healthcare-services marketplace. The identification of these drivers and their directionality, interplay, and magnitude of impact are all of direct relevance to site promoters and managers as well as users. We find that the introduction of doctors’ responses has a significant causal impact on demand-side user perception of medical services offered. More importantly, our research suggests that doctors’ specialty, experience, qualifications, transparency in appointment booking, service fees, and response quality moderate the effect of doctors’ Q&A responses on user recommendations.